Analisis Faktor-Faktor Yang Mempengaruhi Persepsi Wajib Pajak Orang Pribadi Mengenai Penggelapan Pajak pada KPP Pratama Lubuk Pakam - Marlina Marlina (JURNAL PUNDI, 2018)
The purpose of this study was to empirically prove the influence of partially or simultan tax examination intensity, quality of service tax, taxpayer compliance, justice, knowledge and understanding of the taxpayer, the tax system, tax discrimination and the possibility of detection of cheating against the perception of taxpayers about tax evasion on KPP Pratama Lubuk Pakam.The population in this research is the whole personal person taxpayer listed on KPP Pratama Lubukpakam 2015 which amounted to 167,946 people by using the sample Slovin formula according to as much as 100 samples with a proportional random and accidental sampling. Data analysis techniques using multiple linear regression with t-test statistical test, F test and koeficien determination..The results of the study prove that simultan tax examination intensity, quality of service tax, taxpayer compliance, justice, knowledge and understanding of the taxpayer, the tax system, tax discrimination and the possibility of detection of deception effect significantly to taxpayer perceptions about tax evasion.Partially intensity inspection tax, taxpayer compliance, justice, and the possibility of cheating detected no effect on perception of taxpayers about tax evasion, the quality of service of significant negative effect against the taxpayer perceptions about tax evasion, while the knowledge and understanding of the taxpayer, the tax system as well as a significant positive effect of tax discrimination to taxpayer perceptions about tax evasion